2017
DOI: 10.7860/jcdr/2017/28609.10459
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Lipids with Hepatic Steatosis, Stage of Liver Fibrosis and Viral Load in Chronic Hepatitis C

Abstract: Introduction: Hepatitis C Virus (HCV) relies on host lipids for its life cycle contributing to lipid abnormalities and hepatic steatosis. Disease progression is influenced by viral factors interacting with host immune and metabolic pathways. The significance of serum lipids for Chronic Hepatitis C (CHC) assessment is not clearly established yet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Although new and efficient drugs that can safely cure hepatitis C with high rates of sustained virological response have been developed, fibrosis still progresses in some patients with a further risk of cirrhosis and HCC development, mainly in those with advanced fibrosis . Recently, liver steatosis has been described as an additional risk factor for fibrosis progression and HCC development in patients with and without hepatitis C . Hepatic steatosis is defined as excessive fat accumulation in the liver.…”
Section: Introductionmentioning
confidence: 99%
“…Although new and efficient drugs that can safely cure hepatitis C with high rates of sustained virological response have been developed, fibrosis still progresses in some patients with a further risk of cirrhosis and HCC development, mainly in those with advanced fibrosis . Recently, liver steatosis has been described as an additional risk factor for fibrosis progression and HCC development in patients with and without hepatitis C . Hepatic steatosis is defined as excessive fat accumulation in the liver.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, quantitative analysis of serum lipid levels of liver and fat tissues was not conducted. There are several evidences that serum lipid levels such as TG are associated with liver fat or other fat tissues (Huang et al., 2015; Valkov, Ivanova, Alexiev, Antonov, & Mateva, 2017). Thus, in‐depth experiments with more lipid parameters and analysis for the association of serum lipid levels and fat tissues should be conducted in the further study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, quantitative analysis of serum lipid levels of liver and fat tissues was not conducted. There are several evidences that serum lipid levels such as TG are associated with liver fat or other fat tissues (Huang et al, 2015;Valkov, Ivanova, Alexiev, Antonov, & Mateva, 2017).…”
Section: F I G U R Ementioning
confidence: 99%
“…Disease progression is affected by viral factors that interact with the host's immune and metabolic pathways. [25] However, the validity of the use of serum lipids for assessment of CHC severity needs further investigation. In this study, we found that patients with CHC who had higher cholesterol levels had an increased risk of NAFL.…”
Section: Discussionmentioning
confidence: 99%